2013
DOI: 10.1371/journal.pone.0081532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Value of Conventional Ultrasonography and Shear Wave Elastography in the Prediction of Thyroid Lesions Malignancy

Abstract: IntroductionThyroid nodular disease (TND) is a very common disorder. However, since the rate of malignancy is reported to be 3-10%, only a minority of patients require aggressive surgical treatment. As a result, there is a need for diagnostic tools which would allow for a reliable differentiation between benign and malignant nodules. Although a number of conventional ultrasonographic (US) features are proved to be markers of malignancy, Shear Wave Elastography (SWE) is considered to be an improvement of conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 20 publications
1
78
1
Order By: Relevance
“…Other studies suggested that SWE was useful in differentiating benign and malignant thyroid nodules when the cut-off level of 66 kPa and 65 kPa for E maximum were used, respectively [15,36]. However, Szczepanek-Parulska et al [37] found that the threshold value of 50 kPa for E maximum was the most useful SWE parameter in the differentiation of benign and malignant nodules. Using the cut-off value of ≥53.2 kPa for E maximum ≥ 34.5 kPa for E mean and ≥21.8 kPa for E minimum , Duan et al [33], found that SWE was superior to conventional GSU in identifying malignant nodules.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies suggested that SWE was useful in differentiating benign and malignant thyroid nodules when the cut-off level of 66 kPa and 65 kPa for E maximum were used, respectively [15,36]. However, Szczepanek-Parulska et al [37] found that the threshold value of 50 kPa for E maximum was the most useful SWE parameter in the differentiation of benign and malignant nodules. Using the cut-off value of ≥53.2 kPa for E maximum ≥ 34.5 kPa for E mean and ≥21.8 kPa for E minimum , Duan et al [33], found that SWE was superior to conventional GSU in identifying malignant nodules.…”
Section: Discussionmentioning
confidence: 97%
“…The patients with MNG were selected from a group of subjects referred for thyroidectomy between August and December 2010, irrespectively of indications for surgery, described previously [19]. All patients underwent thyroid US and SWE examination prospectively before surgery.…”
Section: Patientsmentioning
confidence: 99%
“…However, due to the long examination time and higher costs, it is not possible to use MRI in daily practice. Shear wave elastography (SWE) is a novel imaging modality, which could give quantitative information regarding the stiffness of tissues and is found effective in the diagnosis of several pathologies including liver fibrosis and malignancies of the breast, thyroid and prostate [3,4] In this paper we will present two cases with penile masses which were evaluated by SWE in addition to MRI to show the possible role of SWE in the differentiation of benign and malignant masses.…”
Section: Introductionmentioning
confidence: 99%